Parental knowledge on preventive and adverse events of fluoridated dentifrices - Coclete, Giovanna Elisa Gabriel [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Castro E Silva, Malena Morais [UNESP]; Sampaio, Caio [UNESP]; Paiva, Mayra Frasson [UNESP]; Silva, Isabela Ferreira da [UNESP]; Monteiro, Douglas Roberto [UNESP]; Hosida, Thayse Yumi [UNESP]; Pessan, Juliano Pelim [UNESP] (My University, 2024)
Purpose: To assess the knowledge of parents/guardians of children considered within the risk range for the development of dental fluorosis on the preventive and adverse effects of fluoride, as well as the relationship with variables related to the use of fluoridated toothpaste by their children. Methods: Interviews (n=398; convenience sample) were conducted at three vaccination centers in the city of Araçatuba (Brazil), using a structured questionnaire comprising items related to the interviewees' education, child’s age and gender, data on brushing habits and use of fluoridated dentifrice, and questions on preventive and adverse effects of fluoride. The amount of toothpaste used was estimated by showing 7 identical toothbrushes with varying amounts of biscuit-simulating toothpaste (previously determined by dentifrice weighing using a precision scale). Data were submitted to Mann Whitney’s, Kruskal Wallis’ and Dunn's tests, and Spearman's correlation coefficient (p<0.05). Results: The interviewees’ schooling was directly related to their knowledge of preventive and adverse effects of fluoride (p<0.05), and inversely related to the amount of dentifrice used by the child (p<0.001). Also, the child's age was inversely related to dentifrice ingestion (during toothbrushing and from the tube) (p<0.001). The type of dentifrice was also influenced by the child's age and the interviewee's schooling (p<0.05). Conclusions: It was concluded that educational strategies targeted at parents/guardians of children are needed to achieve the greatest preventive effect of fluoridated dentifrices with the lowest possible side effects.
Keywords: Child; Dental Caries; Dentifrices; Fluorosis, Dental; Health Education